UNDERSTANDING PHYSICS IDENTITY DEVELOPMENT IN PRESERVICE TEACHERS: THE ROLES OF MOTIVATIONAL AND SOCIAL FACTORS - Nurlina Nurlina (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Physics identity plays an important role in shaping engagement, persistence, and professional readiness among preservice physics teachers (PSPTs). However, the mechanisms underlying its development remain underexplored in teacher-education contexts. This study aimed to examine how self-efficacy, interest, perceived recognition, and sense of belonging interact to shape physics identity among Indonesian PSPTs. A cross-sectional survey was conducted involving 347 PSPTs from several public universities in Indonesia. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) to examine the relationships among the constructs. The results indicate that self-efficacy serves as a foundational predictor that significantly influences interest, perceived recognition, and sense of belonging. These three factors, in turn, contribute significantly to the development of physics identity. Mediation analysis further revealed that interest, recognition, and sense of belonging partially mediated the relationship between self-efficacy and physics identity. Overall, the model demonstrated moderate explanatory power in explaining physics identity among PSPTs. These findings suggest that the development of physics identity among preservice teachers emerges through the interaction of psychological and social factors.